2017
DOI: 10.1055/s-0037-1604091
|View full text |Cite
|
Sign up to set email alerts
|

Platelets as Modulators of Liver Diseases

Abstract: Platelets are key players in thrombosis and hemostasis. Alterations in platelet count and function are common in liver disease, and may contribute to bleeding or thrombotic complications in liver diseases and during liver surgery. In addition to their hemostatic function, platelets may modulate liver diseases by mechanisms that are incompletely understood. Here, we present clinical evidence for a role of platelets in the progression of chronic and acute liver diseases, including cirrhosis, acute liver failure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 144 publications
1
34
0
Order By: Relevance
“…Platelets, another factor of APRI, are reported as an active participant in the process of liver inflammation. 30 Platelets exert potent inflammatory effects and play a central part in the progression from simple steatosis to NASH. 31 Excessive platelet consumption is one of the mechanisms of thrombocytopenia in chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets, another factor of APRI, are reported as an active participant in the process of liver inflammation. 30 Platelets exert potent inflammatory effects and play a central part in the progression from simple steatosis to NASH. 31 Excessive platelet consumption is one of the mechanisms of thrombocytopenia in chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia has been demonstrated to be related to the degree of liver damage in both clinical cases and animal models 4749 . Because the liver is the major organ expressing TPO, discovering thrombocytopenia in patients with chronic liver diseases would be expected 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite severe hepatic dysfunction, serum TPO level was normal and not associated with platelet count in acute liver failure in one study 50 , suggesting that additional pathological factors are more critical. Because coagulation pathways have been demonstrated to be activated during acute liver injury and antiplatelet therapy has decreased liver injury and mortality 48,49,51 , the activation of platelet-related coagulation pathways are likely to be part of the pathophysiology. As the mechanism remains elusive, various candidate pathogenic factors may be involved 5 .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that platelets might also contribute to the development of HCC 1416. Lisman and Luyendyk demonstrated that platelets played an important role in HCC growth and metastasis 17. Meanwhile, platelet lysate has been found to stimulate proliferation of four different HCCs 18.…”
Section: Introductionmentioning
confidence: 99%